Trans-Gulf of Mexico loop migration of tree swallows revealed by solar geolocation. Issue 5 (1st October 2014) - Bradley, David W.; Clark, Robert G.; Dunn, Peter O.; Laughlin, Andrew J.; Taylor, Caz M.; Vleck, Carol; Whittingham, Linda A.; Winkler, David W.; Norris, D. Ryan
Abstract: One of the greatest feats of avian migration is the non-stop crossing of extensive areas of inhospitable habitat such as deserts and seas. Differences in spring and autumn migration routes have been reported in species that cross such barriers, and are thought to have evolved in response to seasonal variation in prevailing wind direction. We tested the hypothesis that migration routes vary seasonally with respect to the Gulf of Mexico in the tree swallow Tachycineta bicolor using solar geolocators attached and retrieved at 4 breeding sites in central North America. We found that 100 % of birds ( n = 10) made a trans-Gulf flight of >850 km from Louisiana south to their wintering grounds in the Yucatan Peninsula in 12–36 hours, achieving minimum ground speeds as high as 32 m/s. Although most days during autumn migration were characterized by unfavorable headwinds blowing to the northwest, migration over the Gulf mostly occurred on days with strong winds blowing to the south. In contrast, in 8 of 9 (88 %) birds on spring migration returned from the wintering grounds towards Louisiana following a clockwise loop pat tern flying over land to the west around the Gulf. During this spring period there were few days with prevailing winds from the south to assist northward migration. Results suggest that, despite being up to three times further (ca. 2, 700 km), a coastal cir- cum-Gulf spring migration represents the less risky route when wind conditions are not favorable. These findings also help to re solve a long-standing dispute in the literature concerning migration patterns between the US Gulf coast and Mexico, and provide insight into the factors shaping migration strategies of small songbirds migrating across large bodies of water.